Synthesis and Antitubercular Activity of Some 4-Thiazolidinones - Solankaee, Anjani; Kapadia, Kishore (Asian Journal of Chemistry, 2010)
Several 2, 3-disubstituted-5 [ω-carboxyhepty]-4-thiazolidinones have been prepared by condensing Schiff bases, from aryl amines and aryl aldehydes with 2-mercaptosebacic acid.